Carbohydrate beliefs and practices of ultra-endurance runners in Ireland for gastrointestinal symptom management - Ryan, Tansy; Daly, Ed; Ryan, Lisa (Frontiers in Nutrition, 2024)
Purpose: This study aimed to investigate the carbohydrate beliefs and practices of ultra-endurance runners in Ireland to gain an understanding of their gastrointestinal symptom (GIS) management strategies. Methodology: An adapted version of a previously developed and validated questionnaire was distributed online to ultra-endurance runners, recognised as those who completed a single bout of exercise lasting four or more hours. Questions related to carbohydrate awareness and sourcing, and dietary practices, particularly in relation to gastrointestinal symptom management. Results: A total of n=68 individuals completed the adapted questionnaire. Of these, n=1 was excluded due to their reporting of an ulcerative colitis diagnosis. The remaining participants included n=46 males and n=21 females. Personal previous experience was the main source directing participants’ nutrition practices (n=30) while only n=3 quoted sourcing information from qualified professionals. n=42 participants experienced GIS, usually equally around training and competition times. Many participants had not previously implemented any specific dietary or non-dietary strategies to alleviate exercise-induced GIS. Supplementing with nitrates (n=9) and probiotics (n=4) were the most common dietary practices to alleviate GIS, while other (n=14) and portion control (n=13) were the most reported non-dietary practice. Discussion: Akin to previous similar literature, these findings suggests that GIS are prevalent in the ultra-endurance running community, regardless of whether during training or an event. Similarly, this research highlights the vast range of GIS experienced by this population. However, the absence in both dietary and non-dietary related practices employed for GIS management alludes to a current deficit in the availability of nutrition information specific to this problem. Further research is required to understand the mechanisms behind ultra-endurance associated GIS and its various management strategies as well as best practices for communicating these to the target audience to reduce individuals risks of developing long-term, chronic health complications